Building a Management Information System with Inter-Agency Data Sharing to Improve Data-Based Decision Making Across Systems: Experiences From Wisconsin PROMISE. (October 2021) - Guentherman, Michael; Hartman, Ellie; Schlegelmilch, Amanda; Brinck, Emily A.; Anderson, Catherine A.
Inter-agency data systems can improve data-based decision making across service systems. The Promoting the Readiness of Minors in Supplemental Security Income (PROMISE) federal research demonstration projects required inter-agency collaboration to provide needed support to youth receiving Supplemental Security Income (SSI) and their families. Wisconsin PROMISE built a system that gathered data from multiple agencies and provided a holistic picture of participants for use in evidence-based decision making. The inter-agency management information system (MIS) supported both formative evaluation of operational activities and short- and long-term impact analyses. Wisconsin PROMISE provided services and collected participant data using information technology (IT) systems distributed across eight different state agencies and multiple divisions within those organizations. The framework implemented for the Wisconsin MIS met the project objectives for an interorganizational data system and addressed the inherent challenges of collecting interorganizational data. The MIS was used for sharing data for both service delivery and research, while providing insight into the effectiveness of PROMISE project initiatives and all agencies serving the individual and their families. The purpose of this article is to share an example of how a MIS was built so others can replicate and/or use lesson learned to build something similar for their own purposes.